From gut to heart: Probiotics-driven cholesterol metabolism, mechanisms and health benefits - Prakash Umapathi; Nivetha Siva; Senthilkumar Balakrishnan; Vincent Savariar; Rasiravathanahalli Kaveriyappan Govindarajan; Andrey Nagdalian; Ivan Evdokimov; Vladimir Kurchenko; Alexey Lodygin; Senbagam Duraisamy (PharmaNutrition, 2026)

Dual scheme biocatalytic pre-treatment and AHL mediated quorum sensing activation to accelerate biofilm formation: A multi-perspective technology for the sustainable biodegradation of marine microplastics - Naveen Nair; Shivangi Dutta; S. Tarun; Muneeswari Rajasekaran; Subhan Kumar Pal; Ravikrishnan Vinu; Senthilkumar Balakrishnan; Ramani Kandasamy (Chemical Engineering Journal, 2025)

Enhanced lipase production and characterization from Aeromonas media VBC8: Applications in biodegradation of lubricating oil waste - Ramalingam Kowsalya; Karunakaran Saravanan; Kandasamy Selvam; Balakrishnan Senthilkumar; Duraisamy Senbagam (Biocatalysis and Agricultural Biotechnology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Enhanced biogas yield in anaerobic digestion of citric acid wastewater by pre-treatment: The effect of calcium hydroxide precipitation and electrocoagulation process - Pinar Belibagli; Habibe Elif Gulsen Akbay; Salih Arslan; Birgul Mazmanci; Nadir Dizge; Natarajan Senthilkumar; Deepanraj Balakrishnan (Process Safety and Environmental Protection, 2024)

Prioritization of chemicals in personal care products based on persistent, bioaccumulative and toxic (PBT) potential: An Indian perspective - Abirami Balakrishnan; Varshini Senthilkumar; Sowmiya Rajan Jeyakumaran; Jabez John; Kevin Vinodh; Uthradevi Kannan; Balakrishnan Paramasivam (Regulatory Toxicology and Pharmacology, 2024)

Bactericidal and non‐cytotoxic activity of bacteriocin produced by Lacticaseibacillus paracasei F9 ‐02 and evaluation of its tolerance to various physico‐chemical conditions - Senbagam Duraisamy; Aswathy Sathyan; Senthilkumar Balakrishnan; Prabhu Subramani; Chidhambaram Prahalathan; Anbarasu Kumarasamy (Environmental Microbiology, 2023)
This study aims to explore novel lactic acid bacteria (LAB) from breast‐fed infants' faeces towards characterizing their antimicrobial compound, bacteriocin. The LAB, Lacticaseibacillus paracasei F9‐02 showed strong antimicrobial activity against clinical pathogens. Their proteinaceous nature was confirmed as the activity was completely abolished when treated with proteinaceous enzymes and retained during neutral pH and catalase treatment. The purified bacteriocin showed antimicrobial activity at the minimum inhibitory concentration (MIC) value of 7.56 μg/ml against vancomycin‐resistant Enterococcus sp. [vancomycin‐resistant enterococcal (VRE)], and methicillin‐resistant Staphylococcus aureus (MRSA), 15.13 μg/ml against Klebsiella pneumoniae , Pseudomonas aeruginosa , Salmonella enterica subsp . enterica serotype typhi and 30.25 μg/ml against Shigella flexneri . Present study also proved the bactericidal, non‐cytotoxic and non‐hemolytic nature of bacteriocin. Additionally, bacteriocin retained their stability under various physico‐chemical conditions, broad range of pH (2–10), temperature (40–121°C), enzymes (amylase, lipase and lysozyme), surfactants [Tween‐20, 80, 100 and sodium dodecyl sulfate (SDS)], metal ions (CaCl 2 , FeSO 4 , ZnSO 4 , MgSO 4 , MnSO 4 , CuCl 2 ) and NaCl (2%–8%). The molecular weight of bacteriocin (~28 kDa) was determined by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE), functional and active groups were assessed by Fourier Transform‐Infrared (FT‐IR). To our knowledge, this is the first study reporting L. paracasei from breast‐fed infants' faeces and assessing their antimicrobial compound, bacteriocin. The study results furnish the essential features to confirm the therapeutic potential of L. paracasei F9‐02 bacteriocin.

Preconcentrations of Pb(II), Ni(II) and Zn(II) by solid phase bio-extractor using thermophilic Bacillus subtilis loaded multiwalled carbon nanotube biosorbent - Sadin Ozdemir; Abdurrahman Dündar; Nadir Dizge; Ersin Kılınç; Deepanraj Balakrishnan; Kashi Sai Prasad; Natarajan Senthilkumar (Chemosphere, 2023)

Phenotypic assessment of safety and probiotic potential of native isolates from marine fish Moolgarda seheli towards sustainable aquaculture - Fazal Husain; Senbagam Duraisamy; Senthilkumar Balakrishnan; Sukumar Ranjith; Prahalathan Chidambaram; Anbarasu Kumarasamy (Biologia, 2022)

Production of eco-friendly PHB-based bioplastics by Pseudomonas aeruginosa CWS2020 isolate using poultry (chicken feather) waste - Sriramani Murugan; Senbagam Duraisamy; Senthilkumar Balakrishnan; Anbarasu Kumarasamy; Prabhu Subramani; Amutha Raju (Biologia Futura, 2021)

Statistical Optimization of Bioprocess Parameters for Improved Production of L-Asparaginase from Lactobacillus plantarum - Sivasankari Mathiyalagan; Senbagam Duraisamy; Senthilkumar Balakrishnan; Anbarasu Kumarasamy; Amutha Raju (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Bacteriocin—a potential antimicrobial peptide towards disrupting and preventing biofilm formation in the clinical and environmental locales - Senbagam Duraisamy; Senthilkumar Balakrishnan; Sukumar Ranjith; Fazal Husain; Aswathy Sathyan; Ansu Susan Peter; Chidambaram Prahalathan; Anbarasu Kumarasamy (Environmental Science and Pollution Research, 2020)

Assessment of Antioxidant, Antibacterial Activities and Bioactive Compounds of the Wild Edible Mushroom Pleurotus sajor-caju - Selvam Kandasamy; Sudhakar Chinnappan; Selvankumar Thangaswamy; Senthilkumar Balakrishnan; Ashraf Y. Z. Khalifa (International Journal of Peptide Research and Therapeutics, 2020)

Antiquorum sensing and antibiofilm potential of biosynthesized silver nanoparticles of Myristica fragrans seed extract against MDR Salmonella enterica serovar Typhi isolates from asymptomatic typhoid carriers and typhoid patients - Senthilkumar Balakrishnan; Kalibulla Syed Ibrahim; Senbagam Duraisamy; Ilakkia Sivaji; Selvam Kandasamy; Anbarasu Kumarasamy; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2020)

Effect of Bacillus cereus peptide conjugated with nanoporous silica on inactivation of Listeria monocytogenes in apple juice, as an ecofriendly preservative - Senbagam Duraisamy; Senthilkumar Balakrishnan; Jayasudha Jayachandran; Fazal Husain; Anbarasu Kumarasamy (Environmental Science and Pollution Research, 2018)

Biosynthesis of silver nanoparticles using Myristica fragrans seed (nutmeg) extract and its antibacterial activity against multidrug-resistant (MDR) Salmonella enterica serovar Typhi isolates - Senthilkumar Balakrishnan; Ilakkia Sivaji; Selvam Kandasamy; Senbagam Duraisamy; Nachimuthu Senthil Kumar; Guruswami Gurusubramanian (Environmental Science and Pollution Research, 2017)

Effect of ompR gene mutation in expression of ompC and ompF of Salmonella typhi - Mahaboobbasha Malickbasha; Ramaiah Arunachalam; Balakrishnan Senthilkumar; Moses Rajasekarapandian; Gurusamy Annadurai (Interdisciplinary Sciences: Computational Life Sciences, 2010)